Leadership Influence Toward Professionalism In Teaching And Learning Quality At Iain Raden Intan Bandar Lampung - Patimah, Siti (Ar Raniry : International Journal of Islamic Studies, 2015)
This research was conducted at IAIN Raden Intan Bandar Lampung which is aimed at revealing the influence of leadership on the lecturers’ professionalism and teaching-learning quality. The study uses a quantitative approach through descriptive correlation technique and regression by using parametric statistical analysis. The research findings show that the three hypothesis can be accepted as supported by empirical as following: 1) the influence of leadership upon lecturers’ professionalism is 12.5%, with the strength low correlation as (0.354); 2) the leadership influence toward the learning quality is 0.81% with a low correlation strength i.e. 0.285; and 3) the lecturers’ professionalism influence on learning quality is equal to 63.9%, with a strong correlation (0.799).